Interstitial Lung Disease in Dermatomyositis Without Myositis-Specific and Myositis-Associated Autoantibodies: Study of a Series of 72 Patients From a Single Cohort - Chen, Fang; Wang, Jinping; Zhang, Puli; Zuo, Yu; Ye, Lifang; Wang, Guochun; Shu, Xiaoming (Frontiers in Immunology, 2022)
Objective The clinical features of interstitial lung disease (ILD) in patients with dermatomyositis (DM) and negative myositis autoantibodies had not been exactly demonstrated previously. This study aimed to describe and expand the phenotype of interstitial lung disease (ILD) in this cohort of patients. Methods A total of 1125 consecutive Chinese patients with idiopathic inflammatory myopathies (IIM) between 2006 and 2020 were screened retrospectively. All proven cases of isolated ILD with both negative myositis-specific autoantibodies (MSA) and negative myositis-associated autoantibodies (MAA) were selected for inclusion. The clinical features and outcome among this group, MDA5+DM (DM patients with positive anti-MDA5 antibody) and ASS (patients with positive anti-aminoacyl tRNA synthetases antibodies were recorded and compared. Results Of 1125 IIM patients with an average follow-up of 6 years, 154 DM patients with negative MSA and MAA (MSA/MAA) were identified, with an ILD incidence of 46.8%. DM-ILD Patients with negative MSA/MAA presented younger age at onset (p<0.001), lower incidence of elevated CA153 (p=0.03) and fever (p=0.04)than those ILD patients with MDA5+DM and ASS.The estimated high-resolution computed tomography patterns of ILD showed non-specific interstitial pneumonia (66.6%), followed by organizing pneumonia in patients with negative MSA/MAA. OP pattern was more common in patients with MDA5+DM (69.7%), and the ratios of the OP (48.7%) and NSIP (51.3%) patterns were almost equal in patients with ASS. Of these DM-ILD patients with negative MSA/MAA, 25% developed rapidly progressive interstitial lung disease (RP-ILD). Patients with RP-ILD had a shorter disease duration (p=0.002), higher percentage of positive ANA(p=0.01) and organizing pneumonia patterns (p=0.04), elevated CYFRA211(p=0.04) and decreased FiO2/PaO2 (p<0.001) than those with chronic progressive ILD. The incidence of OP pattern in RP-ILD patients with negative MSA/MAA was lower than in those RPILD patients with MDA5+ DM (75%) and ASS (89%) (p=0.006). The cumulative 5- and 10-year survival rates in the DM-ILD patients with negative MSA/MAA were 91% and 88%, respectively, during the long-term follow-up study. And they had more favorable survival rate compared with ILD patients with MDA5+DM and ASS (p<0.001). An independent prognostic factor was identified as decreased PaO2/FiO2 (hazard ratio, 0.97; p=0.004]. Conclusions This study indicates DM-ILD patients with negative MSA/MAA had favorable long-term outcomes. Decreased baseline PaO2/FiO2 acted as an independent prognostic factor for this group of patients.